Productivity : identification and classification of factors affecting productivity in the construction of a large-diameter pipeline project - Grobler, J. J.(Johannes Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Ing.) -- University of Stellenbosch, 1992.